Floating 3D-PDMS-Iron oxide molecular baskets for decontaminating diverse pollutants and analyzing structural composition impacts - Sethu Kalidhasan; Jonghoon Choi; Hee-Young Lee (npj Clean Water)
Abstract Novel iron oxide-incorporated porous polydimethylsiloxane sponges were developed using a simple, non-toxic two-step process. Characterized through various techniques, these sponges serve as effective photocatalysts, absorbents, and adsorbents for pollutant removal. They demonstrated nearly 100% degradation of rhodamine B under optimal conditions ( ~ 100% with Xe arc lamp, 50 mg, pH 3-9, and 4 h), following a pseudo second-order kinetic model (r2 = 0.9999). The sponges also exhibited good activity for other pollutants, including methylene blue (76–87%), 1,4-dichlorobenzene (57–71%), and azithromycin (82–87%), and maintained high performance over 11 reuse cycles with minimal iron loss. In addition, fresh and used catalysts effectively separated oils (173–680 mg with 50 mg of absorbent, and 10–15 s) and chromium (VI) [~87% with 1 ppm, 50 mg, pH 7, and 24 h] from water. This environmentally sustainable approach produces no toxic waste and allows for simple regeneration, making it a promising solution for the water treatment industry.